Saturated ablation in metal hydrides and acceleration of protons and deuterons to keV energies with a soft-x-ray laser. - Andreasson, J; Iwan, B; Andrejczuk, A; Abreu, E; Bergh, M; Caleman, C; Nelson, A; Bajt, S; Chalupsky, J; Chapman, H; Fäustlin, R; Hajkova, V; et al. (2011)
Studies of materials under extreme conditions have relevance to a broad area of research, including planetary physics, fusion research, materials science, and structural biology with x-ray lasers. We study such extreme conditions and experimentally probe the interaction between ultrashort soft x-ray pulses and solid targets (metals and their deuterides) at the FLASH free-electron laser where power densities exceeding 10(17) W/cm(2) were reached. Time-of-flight ion spectrometry and crater analysis were used to characterize the interaction. The results show the onset of saturation in the ablation process at power densities above 10(16) W/cm(2). This effect can be linked to a transiently induced x-ray transparency in the solid by the femtosecond x-ray pulse at high power densities. The measured kinetic energies of protons and deuterons ejected from the surface reach several keV and concur with predictions from plasma-expansion models. Simulations of the interactions were performed with a nonlocal thermodynamic equilibrium code with radiation transfer. These calculations return critical depths similar to the observed crater depths and capture the transient surface transparency at higher power densities.